Functional variation reflects intra-strain diversity of Staphylococcus aureus small colony variants in the host-pathogen interaction - Hilmi, Dina; Parčina, Marijo; Bode, Konrad A.; Ostrop, Jenny; Schuett, Sabine; Heeg, Klaus; Ziebuhr, Wilma; Sommerburg, Olaf; Bekeredjian-Ding, Isabelle (International journal of medical microbiology, 2013)
It is well acknowledged that genetic variation accounts for the intra-species variability in Staphylococcus aureus isolates. Similarly, deficiency in DNA repair and the resulting increase in genomic mutations determine intra-strain variability in S. aureus small colony variants (SCV). The aim of this study was to investigate whether intra-strain diversity would be associated with an alteration of the host-pathogen interaction. To this end, biofilm formation and immune stimulatory capacity were compared in consecutive SCV isolates originating from a single patient. Despite the relatedness of the isolates, the results revealed significant differences in biofilm formation and immune stimulation determined by Toll-like receptor-2 (TLR2) activity. Variation in the extent of biofilm production could be attributed to differences in the expression of protein A (SpA) and agrA. TLR2 activity only partially correlated with these parameters. Although transiently increased functional activity correlated with clinical remission and was abrogated in MRSA superinfection, we can only speculate that changes in the SCV phenotype reflect alterations in the microbial environment and/or treatment. Taken together, our study provides in vivo evidence for the functional consequences of intra-strain variation in S. aureus.
Gesehen am 25.05.2021